The Obrenović Princely Court in Požarevac - Borić, Tijana S. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The princely court in Požarevac was built suddenly in just two months in early 1825 when Prince Miloš recognised that he had to visualise his presence and reaffirm his authority within the rebellious group of Serbian people who were at the strategic location both for the Principality of Serbia and the commercial affairs of the Prince. With the konaks and the church built, Požarevac started developing into the second capital of the Principality of Serbia, attracting many domestic people and foreign visitors. Shaped as typical konak, a residence of elite members of the Ottoman society, the court in Požarevac reveals Prince Miloš’s representative strategy. The interior of both konaks outlines awareness of European trends in shaping the seat of the head of the state. The closeness of the church and frequent attendance of the members of the royal family and their official guests to the services point to the close and interconnected relationship between the state and the church in 19th-century Serbia.